Effect of Various Sodicity Levels on Ionic Relations in Clonal Eucalyptus plantation - Camus, David; Garg, Rakesh K.; Sharma, Charulata (Indian Forester, 2021)
The present study aimed at understanding the effect of soil sodicity on physiological mechanisms and biochemical traits of Eucalyptus tereticornis clonal plantation under sodic soils with soil pH level ranging upto 10.0 and high Sodium Adsorption Ratio (SAR). Study was carried out in one and two year old Eucalyptus tereticornis field plantations. The results indicated increased proline content in plants growing under higher pH level. Plants growing on the soils of lower pH ranges (<8.2) recorded high chlorophyll content than trees growing under higher pH (>9.21) in first year (2.024ug/g FW) and second year old (1.931 ug/g FW) plantations. Sodium ions in the soil varied from 2.725 to 15.428 meq/L. Level of sodium ion uptake by leaves ranged between 0.12 to 0.13 per cent. The low sodium content in leaves favoured more uptake of potassium ions.